Food problem and its solution - Vlasov, V. (Acta Agraria Debreceniensis, 2014)
The Globalization processes substantially changed relations between countries. One of main factors of these processes is forming in ХХ century of Worldwide auction organization, which activity provided with swift growth of volumes in trade of food commodities. Thus, the solution for global food problem was found. At the end of the second half of ХХ century the production volumes of agrarian goods in countries with a different level of economic development grew considerably. However, a food crisis 2007–2008 led to the necessity to define factors, which would allow to grow production, converting an agrarian sector into sustainable growing industry, passing ahead the increase of quantity of population.